Theory and Practice of Natural Computing 5th International Conference, TPNC 2016, Sendai, Japan, December 12-13, 2016, Proceedings - Martín-Vide, Carlos; Mizuki, Takaaki; Vega-Rodríguez, Miguel A. (Theoretical Computer Science and General Issues, 2016)
This book constitutes the refereed proceedings of the 5th International Conference on Theory and Practice of Natural Computing, TPNC 2016, held in Sendai, Japan, in December 2016. The 16 revised full papers presented together with one invited talk in this book were carefully reviewed and selected from 33 submissions. The papers are grouped in topical sections on applications of natural computing, evolutionary computation, formal models, and machine learning.